De cómo convertir un texto expositivo en argumentativo y sus implicaciones didácticas - Perelló Marugán, David; Pintos López, Marta; Álvarez Angulo, Teodoro (Didáctica. Lengua y Literatura, 2007)
This article aims to show the conversion from a narrative text into a more persuasive one, which involves to take into account the production process through the consideration of an addressee, the intention, the structure and the textual language marks of both of them. The article tries to guide in a didactic way the transformation process when contributing at the same time to develop the critical analysis. Cet article nous montre la conversion d´un texte expositif vers un autre argumentatif/ persuasif, ce qui entraîne le fait d´avoir en compte le processus de production à travers la considération d´un destinataire, de l´intention, de la structure et des marques linguistiques textuelles de tous les deux. L´article essaie d´orienter d´une façon didactique le processus de transformation au même temps que contribue à développer l´analyse critique.